Clinical relevance of radiographic linear branching mineral opacities in the canine liver. (6th December 2017) - Genain, M.‐A.; Barbosa, A.; Herrtage, M.; Watson, P.
Abstract : Objectives: To assess the prevalence, clinical significance and breed distribution of linear branching mineralisation superimposed on the hepatic radiographic silhouette in dogs. Materials and Methods: Retrospective review of radiographs or ultrasound images of dogs showing branching mineralisation in the liver. Results: Over the 30‐year review period, 17 cases were identified and the mineralisation had a predominantly ventral distribution. Seven of the 17 were cavalier King Charles spaniels, and four of the total 17 dogs were diagnosed with hepatobiliary system disease. Five dogs had repeat radiographs, of which four showed no change in the pattern and one developed the pattern 6 years after being diagnosed with cholangiohepatitis. Serum calcium concentrations were normal in all patients. Liver enzymes were markedly elevated only in the dog diagnosed with cholangiohepatitis. Histology performed on three patients showed no convincing evidence of primary liver disease. Clinical Significance: Branching mineralisation in the liver parenchyma is a rare finding in dogs with little or no clinical significance and cavalier King Charles spaniels may be predisposed. Biopsy of the liver of affected dogs with no clinical or clinicopathological evidence of liver disease is unlikely to be helpful in these cases.